Comparison of the toxicity of waters containing initially sulfaquinoxaline after photocatalytic treatment by TiO2 and polyaniline/TiO2. Issue 3 (28th January 2021) - Sandikly, Nahid; Kassir, Mounir; El Jamal, Mouhieddine; Takache, Hosni; Arnoux, Philippe; Mokh, Samia; Al-Iskandarani, Mohammad; Roques-Carmes, Thibault
ABSTRACT: This paper addresses the residual toxicity of waters after photocatalysis treatments . The initial waters contain 7 mg L −1 of sulfaquinoxaline (SQX) which is a sulfonamide antibiotic generally recorded inside the water. The contaminated waters are treated by photocatalytic degradation process with bare titania and titania covered with polyaniline (PANI) conducting polymer. The degradation of SQX is conducted at different pH in order to find the optimal condition to obtain SQX concentration relatively equal to zero in the shortest amount of time. This occurs for PANI/TiO2 at pH 12 and TiO2 at pH 4. Toxicity assays (concentration of biomass, pigmentation tests, and cells counting) are undertaken on the microalgae Chlorella vulgaris in order to evaluate the residual toxicity of the 2 treated waters. The toxicity results highlight that the water treated by PANI/TiO2 at pH 12 is the less toxic towards the algae cells. The water processed by bare titania at acidic pH displays unneglectable toxicity towards the algae cells which are larger than the toxicity of the original SQX solution. GRAPHICAL ABSTRACT: UF0001